Exploring the Link between Iron Status and Catalase Activity in Type 2 Diabetes Mellitus - Oleiwi , Esraa H.; Hussein , Saba Z. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Catalase is an antioxidant enzyme found in all living organisms that is responsible for the degradation of hydrogen peroxide, a type of harmful compound known as reactive oxygen species (ROS), into harmless oxygen and water. It is necessary for cell protection from ROS-induced oxidative damage in type 2 diabetes mellitus (T2DM) individuals. T2DM is rapidly rising in prevalence worldwide, emerging as a significant public health challenge. It can disrupt iron regulation in the bloodstream, leading to the production of ROS, which can damage the cells.Objective: To explore the correlation between iron status and catalase activity in T2DM patients, and the possibility of using it as a predictor for the onset and severity of diabetes.Methods: One hundred and fifty participants were included in the study, comprising 50 healthy volunteers who served as the control group (C) and 100 cases diagnosed with T2DM who were divided into three groups based on the duration of their disease: Group A1 (n=38; < 5 years), A2 (n=37; 5-10 years) and A3 (n=25; >10 years). The participants were recruited from the Al-Kindi Teaching Hospital, Baghdad, during the period from October 2022 to the end of January 2023. The study assessed various blood markers in all participants, including Fasting blood glucose (FBG), glycosylated hemoglobin A1c (HbA1c), Iron, total iron binding capacity (TIBC), unsaturated iron binding capacity (UIBC), ferritin, transferrin, a saturation of transferrin (S.Trans) and catalase activity (CAT).Results: Compared to the control group, patients with T2DM showed significantly higher levels of FBG, HbA1c, and ferritin, notably lower levels of iron, TIBC, UIBC, and S.Trans. Interestingly, only the A2 group had significantly lower transferrin levels compared to control. There was a significant decrease in catalase activity across all patient groups. Additionally, a positive correlation was observed between iron levels and catalase activity in all patient groups.Conclusion: Increases in ferritin levels might be a risk factor for developing T2DM. The observed association between lower iron levels and reduced catalase activity in T2DM is intriguing and can serve as a future predictor for the onset and severity of diabetes, warranting further investigation.